A cost-effective counterfeiting prevention method using hashing, QR code, and website - Hossain, Monir; Begum, Momotaz; Das, Bimal Chandra; Uddin, Jia (International Journal of Advances in Applied Sciences, 2024)
In this paper, we proposed a cost-effective software method to prevent counterfeiting where we used a website, quick-response (QR) code, and hashing. At the early stage of the product, the system will create a unique ID and a password with a random password generator for all products. Then, the password hash would be stored along with the ID in the database. At the same time, the password would be converted into a QR code for each product. The manufacturer will collect the QR code and ID and attach them to the product. When consumers attempt to verify the product, they will enter the website provided by the manufacturer and scan the QR code. After applying the same hash used before, the code will be checked on the database. After a successful check, the product entity will be destroyed and the life of the product ends. This paper contains flowcharts, figures, cost estimation, and a detailed explanation of the system. As it only requires domain hosting, thus the fixed cost of the system is so lower to bear for small enterprises also. We built a similar system using PHP, HTML, JavaScript for websites, and MYSQL for databases.